2022
DOI: 10.1007/s00415-022-11312-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of digital technology to evaluate motor function and disease progression in motor neuron disease

Abstract: Amyotrophic lateral sclerosis (ALS) is the most common subtype of motor neuron disease (MND). The current gold-standard measure of progression is the ALS Functional Rating Scale—Revised (ALS-FRS(R)), a clinician-administered questionnaire providing a composite score on physical functioning. Technology offers a potential alternative for assessing motor progression in both a clinical and research capacity that is more sensitive to detecting smaller changes in function. We reviewed studies evaluating the utility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 50 publications
(135 reference statements)
0
11
0
Order By: Relevance
“…Although mostly studied as a proof-of-concept in ALS, 14 previous research has shown the feasibility of accelerometery, demonstrating significant correlations with the ALSFRS-R. 19 , 20 , 21 , 22 , 23 , 24 This study additionally delineated the relationship between the longitudinal trajectory of VMI and overall survival, and demonstrated its ability to differentiate between fast- and slow-progressing patients. This holds significance as it aids in interpreting effect sizes in terms of clinical relevance, thereby contributing to the translation of accelerometer-derived markers to meaningful outcomes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Although mostly studied as a proof-of-concept in ALS, 14 previous research has shown the feasibility of accelerometery, demonstrating significant correlations with the ALSFRS-R. 19 , 20 , 21 , 22 , 23 , 24 This study additionally delineated the relationship between the longitudinal trajectory of VMI and overall survival, and demonstrated its ability to differentiate between fast- and slow-progressing patients. This holds significance as it aids in interpreting effect sizes in terms of clinical relevance, thereby contributing to the translation of accelerometer-derived markers to meaningful outcomes.…”
Section: Discussionmentioning
confidence: 79%
“…Contrarily to survey-based methods, outcomes based on digital health technology purposely assess only one disease domain (e.g., speech, motor, or respiratory function) and allow for an objective and detailed assessment, potentially improving their quantification of domain-specific disease progression. 11 , 12 , 13 For the assessment of motor function, various devices have been developed, 14 collecting data during specific exercises or obtaining data passively throughout the day. Advantages of outcomes derived from passive monitoring are that they are not bound to the patient's ability to complete a specific exercise, may have higher compliance, 15 and may better reflect the patient's real-world functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 , 19 , 41 In addition, there are evolving technical solutions for different impairments, such as high-tech augmentative and alternative communication technologies. 17 , 42 Furthermore, remote settings showed to be supportive of involving family members and assistant nurses in both ALS care and participatory research. 12 , 19 , 41 …”
Section: Discussionmentioning
confidence: 99%
“…Quantitative motor outcome measures may be task-based (i.e., measuring behavior during performance of a specific task) or task-free, where an individual's natural behavior is measured passively and continuously at home. There has been recent development of several task-based approaches to quantify speech and limb function in ALS using scalable technologies at home 9,[16][17][18] and only a single report of a task-free approach in ALS using a waist-worn accelerometer 19 . Task-based measures, however, have some of the same limitations as rating scales in that they are based on a relatively small number of data samples and cannot easily account for diurnal and day-to-day variability, they rely on the participant's ability and motivation to perform the task, and they are susceptible to learning and placebo effects.…”
Section: Introductionmentioning
confidence: 99%